Dairy Fat Intake, Plasma Pentadecanoic Acid, and Plasma Iso-heptadecanoic Acid Are Inversely Associated With Liver Fat in Children. Issue 4 (April 2021) - Sawh, Mary Catherine; Wallace, Martina; Shapiro, Emma; Goyal, Nidhi P.; Newton, Kimberly P.; Yu, Elizabeth L.; Bross, Craig; Durelle, Janis; Knott, Cynthia; Gangoiti, Jon A.; Barshop, Bruce A.; Gengatharan, Jivani M.; et al.
ABSTRACT: Objectives: We sought to evaluate the relevance of pediatric dairy fat recommendations for children at risk for nonalcoholic fatty liver disease (NAFLD) by studying the association between dairy fat intake and the amount of liver fat. The effects of dairy fat may be mediated by odd chain fatty acids (OCFA), such as pentadecanoic acid (C15:0), and monomethyl branched chain fatty acids (BCFA), such as iso-heptadecanoic acid (iso-C17:0). Therefore, we also evaluated the association between plasma levels of OCFA and BCFA with the amount of liver fat. Methods: Observational, cross-sectional, community-based sample of 237 children ages 8 to 17. Dairy fat intake was assessed by 3 24-hour dietary recalls. Plasma fatty acids were measured by gas chromatography-mass spectrometry. Main outcome was hepatic steatosis measured by whole liver magnetic resonance imaging proton density fat fraction (MRI-PDFF). Results: Median dairy fat intake was 10.6 grams/day (range 0.0–44.5 g/day). Median liver MRI-PDFF was 4.5% (range 0.9%–45.1%). Dairy fat intake was inversely correlated with liver MRI-PDFF ( r = −0.162; P = .012). In multivariable log linear regression, plasma C15:0 and iso-C17:0 were inverse predictors of liver MRI-PDFF (B = −0.247, P = 0.048; and B = −0.234, P = 0.009). Conclusions: Dairy fat intake, plasma C15:0, and plasma iso-C17:0 were inversely correlated with hepatic steatosis in children. These hypothesis-generating findings should be tested through clinical trials to better inform dietary guidelines. Abstract : Supplemental Digital Content is available in the text